Exploring Students' Perception of English Speaking through Outdoor Learning Activities - Polis, Felyks Deka; Budi Lestari, Sri Ayu; Anwar, Indry Widyasti (FKIP Universitas Khairun, 2025)
This study explores students' perceptions of English speaking through outdoor learning activities in the English Language Education Study Program of Khairun University. Employing a mixed-methods approach, 30 students participated in the research. Data were collected through questionnaires and interviews, and analyzed quantitatively and qualitatively. The results showed that outdoor English speaking activities can effectively enhance students' confidence, motivation, comfort, engagement, and vocabulary acquisition. Students also perceived that learning outside the classroom provides an opportunity for spontaneous interaction, reduces anxiety, and encourages authentic language use. Outdoor learning also created a supportive environment that encouraged collaboration among peers. These findings suggest that speaking activity in an outdoor setting is an effective teaching method and offers a holistic approach to language learning.